(untitled) (European Journal of Pure and Applied Mathematics, 2025)
This paper deals with the concept of strongly θ(τ_1,τ_2)-continuous functions. Furthermore, some characterizations and several properties concerning strongly θ(τ_1,τ_2)-continuous functions are considered.